Numerical Simulation of a Novel Hydrocyclone Mixer Structurally Optimized for Mixing Performance and Energy Efficiency - Jiale Li; Li Dai; Long Li; Penghui Zhou; Dingliang Xu; Lin Zeng (International Journal of Chemical Engineering)
Energy efficiency of coal-water slurry mixing determines its application and transportation efficiency. This study compares the hydrodynamic characteristics and mixing performance of five different configurations of hydrocyclone mixers under turbulent flow conditions. Numerical calculations were used to investigate the velocity, pressure, and concentration fields of the mixer. Attempts were made to decrease the tangential inlet size and to design indentation structure to control the velocity and pressure fields inside the hydrocyclone mixer, thereby increasing the degree of mixing (DOM) and reducing mixing energy cost (MEC). The findings indicate that better mixing and dispersion can be achieved while reducing energy costs by designing the indentation structure and decreasing the size of the tangential inlet and outlet. It offers a reliable solution for uniformly mixing and dispersing coal-water slurry with organic waste liquids and other highly concentrated fuels.